Effect of air flow rates on concurrent supply and exhaust kitchen ventilation system - Yi, Kun Woo; Kim, Young Il; Bae, Gwi-Nam (SAGE PUBLICATIONS LTD, 2016)
Concurrent supply and exhaust ventilation (CSEV) has been developed to effectively exhaust heat and contamination from the kitchen. The objective of this research was to investigate the performance variation of this system with respect to air flow rates. CSEV system can block the contaminated air from entering the inner space by supplying fresh air horizontally in the ceilings towards the hood where the overflowed contaminated gas tends to diffuse to inner part of the room. The system captures contaminated air in an area near the ceiling and this captured air is then exhausted through the ceiling outlet. For quantitative evaluation, heat and gas capture efficiencies were defined and calculated. Experiments were conducted to compute heat and gas capture efficiencies based on the temperature and SF6 concentration data that were measured at the exhaust locations. To find optimum operation conditions for a CSEV system, numerical analysis was carried out. The numerical results were in good agreement with the experimental values. Maximum differences between the two methods are 17% for hood system and 10% for CSEV. Both heat and gas capture efficiencies would increase as exhaust flow rate of the hood increases. However, the optimum supply flow rate of ceiling nozzle was found to be 100m(3)/h for maximum efficiency. This optimum flow rate condition would improve removing heat and contamination from the kitchen for better indoor air quality.
Keywords: CFD; PERFORMANCE; QUALITY; SIMULATION; STRATEGIES; REMOVAL; COOKING